Pendekatan Remote Auditing Untuk Internal Audit Dalam Mendeteksi Kecurangan (Fraud) Pada Masa Pandemi Covid-19 - Defriko Gusma Putra (Jurnal Ecogen, 2021)
The worsening economic conditions and weak supervision and the distorted focus of companies in facing the Covid-19 pandemic crisis open opportunities for fraudsters in companies that take advantage of the conditions to take actions that harm the company. The Covid-19 pandemic currently occurring has also affected work activities and the internal audit audit process that have been previously determined due to the imposition of PSBB and the prohibition of face-to-face activities so that it has an impact on obtaining audit evidence from restrictions on travel access to checkpoints in several areas. This research is expected to provide insights and solutions related to the application of a remote auditing approach to internal audit in detecting fraud during the Covid-19 pandemic. During the Covid-19 pandemic, remote auditing was the right choice to implement with the various advantages and disadvantages of remote auditing itself, remote auditing became an alternative so that work activities and the inspection process could continue and the role of internal audit in realizing added value for the company to assist management and directors in improving the internal control process and optimizing the detection of fraud.